The Impact of The Development of The Warehouse Market on The Local Community on The Example of The Stryków Commune - Mariusz WOŹNIAKOWSKI; Krzysztof FORTUNA (Communications of International Proceedings, 2022)
In the last decade, the logistics industry in Poland has developed very dynamically. This is also visible on the warehouse market of Central Poland, the third largest market in the country, where Stryków has become an extremely attractive investment area. The convenient location near the intersection of two international communication arteries, i.e. the A1 and A2 motorways, and several important national roads made it a very attractive location for logistics companies, with approx. 4 million sq m of warehouse space, where several large logistics parks, where over 40 companies operate, providing employment to 2,000 people. employees, not only from within the municipality, but also from outside its borders. The effects of this are visible in the structure of the budget of the Stryków Commune. This publication presents the warehouse market of the Stryków Commune. It is one of the oldest logistics and warehouse centers in Poland, offering over 1,000 hectares for investments in the spatial development plan, attracting interested parties not only from Europe, but also from abroad. In the following part, an attempt was made to determine the impact of the warehouse market on the local community of the analyzed commune. The publication is based on the literature on the subject and available industry reports on the warehouse market in Poland. Analyzing reports on the warehouse space market in Poland, it is clear that this market is getting better and better results year after year and is currently the most dynamically developing commercial real estate sector. Currently, the best situation is shown by warehouses from the western regions of the country. Recently, the interest of investors and tenants in locating warehouses in Central Poland has also increased. These areas are quite attractive due to low rent rates and better infrastructure.
Keywords: warehouse market; warehouse; warehouse space; lodzkie voivodeship; Stryków commune